Investigation of the physico-chemical parameters of the «Gelamil» series starches in the technology of mashed soups - Andrieieva, Svitlana; Pyvovarov, Yevgen (Technology audit and production reserves, 2021)
The object of research is the technologies for the production of puree soups using modified starches of the «Gelamil» series. One of the main requirements for the quality of the technology of puree soups is the creation of a fluid, uniform, finely ground texture, which plays a special role in the organoleptic characteristics of this type of product. The texture of the product can be adjusted by adding liquid boiling modified starches. Starches of the «Gelamil» series are represented by potato starch with a reduced viscosity and are characterized as air-flowing gelling potato starch, that is, starch, the solution of which gives a low viscosity at high temperatures, and when solidified – a dense gel. Hydrodynamic changes in the parameters of starch paste based on starches of the «Gelamil» series, depending on the temperature and type of starch, have been established. It was determined that starch paste based on starches of the «Gelamil» series, in comparison with native potato starch, have a low temperature of maximum viscosity from 47±2 °C to 57±2 °C, and thus form a paste with a viscous-flowing texture. The effective viscosity of starch paste was investigated depending on the starch content. It has been experimentally established that regulation of the starch content makes it possible to create starch paste according to different textural properties. For viscous-thinned dispersions, the starch concentration is from 1.0 to 3.0 %. For viscous-flowing dispersions having a long texture, the starch concentration is 3.5 to 5.0 %. For viscous-flowing dispersions having a short texture, the starch concentration is 5.5 to 7.0 %. For the content of native potato starch in the system of more than 5.0 %, a dense paste with a short texture is formed. It was found that for a starch paste based on starches of the «Gelamil» series, the separation of the liquid phase occurs due to 2:00 in an insignificant amount. A lot of components and model systems based on vegetable, legume purees and starch paste have been investigated. It has been determined that, depending on the type of vegetable and legume raw materials, the use of starches of the «Gelamil» series of different types and concentrations depends.